The Effectiveness of using Electronic Commerce Mobile Applications During Covid-19 Pandemic - et. al., Yousef A. Baker El-Ebiary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
E-Commerce has been one of the human needs all around the world. Not only to a customer but also to industry players. The food delivery service industry is one of the E-commerce services. Food delivery is growing up and has a good potential rate in Malaysia and globally now. At first many of Malaysians were still not exposed to food delivery has many advantages, with social distancing the new norm, consumers are demanding to have takeout food delivered in parallel with government standard procedure in the Covid-19 pandemic. To reach people with online business, e-commerce makes an application as initiative to do business via the Internet. E-commerce has many system applications which are product or service system and food system. Product or service system will do business related with product or service meanwhile food system will do business related with food. While running a business via online, there is advantages and disadvantages that will give many impacts in customers, sellers and an application itself. So, the method or strategy to improve the online business which is sample size, measurement and data analysis developed so that online business can run smoothly according to planning.